Strategies Used in the Translation into Albanian of Allusions in Walt Whitman's Poetry - Pema, Alketa (Mediterranean Journal of Social Sciences, 2012)
A translator who examines a text with a view to translate it will have a number of concerns. Among them, allusions arelikely to become puzzles when they cross a cultural divide. Translating allusions can be a demanding task due to the fact thatthey simultaneously activate two texts and have specific meanings in the culture and language in which they arise but notnecessarily in others. However, the use of allusions by an author shows an expectation that the reader is familiar with thereferences made, otherwise the effect is lost. Taking this into account, the present study focuses on personal proper noun andkey phrase allusions in the poems of the- famous American poet Walt Whitman and their translations into Albanian. It aims toinvestigate how translation- strategies would provide the translators, in particular the novice ones, with useful insights concerningintertextual references in general and allusions in particular in order that the translators might find it no more challenging a task.In order to achieve the above mentioned purpose, the personal proper noun and key-phrase allusions in Leaves of Grass andtheir equivalents in the Albanian translation were first identified. Then, Leppihalme's (1997) proposed strategies for thetranslation of allusions were analyzed. The analysis revealed that the most common strategy for the translation of personalproper nouns was that of 'retention without any guidance' and for key-phrase allusions was that 'literal translation with minimumchange'. This is indicative of the translator's wish to be as faithful as possible to the source texts to demonstrate that the allusivelanguage of the original texts and connotations conveyed by them were largely ignored by the translator.